PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO TUTORIAL PENATAAN SANGGUL EVENING STYLE DENGAN MENGGUNAKAN TEKNIK ANYAM PADA SISWA KELAS XI TATA KECANTIKAN DI SMK NEGERI 6 SURABAYA - Juliag, Adila Rachmah; Octaverina Kecvara Pritasari; Sri Usodoningtyas; Biyan Yesi Wilujeng (Jurnal Tata Rias, 2025)
Lack of diversity in material delivery strategies, limited practical facilities, and not optimal utilization of technology-based media result in the learning process of skills running less effectively, so media development is needed that is able to facilitate learning visually, flexibly, and easily accessible. The purpose of this research is to create learning video media that is valid, practical, and effective for learning evening style bun styling with plaiting techniques. ADDIE was used as the development model in this research. Respondents consisted of 37 students of class XI of the Beauty Cosmetology specialty program. Data collection techniques include observation, cognitive tests, psychomotor assessments, and student response questionnaires. The results of this study indicate that: (1) Based on the assessment of media, material, and language aspects, an overall average score of 3.66 was obtained which was classified as “very feasible”. (2) Statistical analysis of cognitive results showed an increase in average results reaching 85. Meanwhile, psychomotor learning outcomes showed an average of 86, which is higher than the KKTP 75 indicating that students have achieved overall completeness. (3) With a student response percentage of 90.71%, which is classified in the “very good” category, it can be concluded that this media has a high level of effectiveness in its use. Thus, the video tutorial media for styling evening style bun with plaiting technique is declared feasible to use because it is practical, effective and gets a positive response from students.